High-entropy metal oxide catalyst, preparation method thereof and application of high-entropy metal oxide catalyst in CO catalytic oxidation

The synthesis of high-entropy metal oxide catalysts by hydrothermal method solves the problem of insufficient catalytic activity of transition metal oxides in low-temperature humid flue gas, and achieves an efficient and low-cost CO catalytic oxidation effect, which is particularly suitable for flue gas treatment in the steel industry.

CN120361915APending Publication Date: 2025-07-25CENT SOUTH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510364516.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The existing transition metal oxide catalysts have insufficient catalytic activity in low-temperature humid flue gas and have poor water resistance and sulfur resistance, making it difficult to effectively treat CO in sintered flue gas in the steel industry.

Method used

The hydrothermal method is used to synthesize high-entropy metal oxide catalysts, form a uniform solution under the action of dispersant, control the addition of alkali precipitant and quench treatment, avoid the agglomeration of nanoparticles, and obtain a special nanosheet structure, ensure uniform dispersion of polymetal ions, and improve the stability and activity of the catalyst.

Benefits of technology

It exhibits excellent CO catalytic oxidation activity at low temperatures, is suitable for complex flue gas treatment, reduces costs, improves CO removal efficiency, and extends the life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120361915A_ABST
    Figure CN120361915A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy metal oxide catalyst as well as a preparation method and application thereof in CO catalytic oxidation, and belongs to the technical field of flue gas treatment. The preparation method comprises the following steps: dissolving copper salt, manganese salt, cerium salt, cobalt salt, vanadium salt and a dispersing agent into water to form a uniform solution, and slowly adding excessive alkali precipitant into the uniform solution to form a solid-liquid mixture; the solid-liquid mixture is transferred into a high-pressure kettle to be subjected to a hydrothermal reaction and then quenched, an obtained hydrothermal reaction product is calcined, and the high-entropy metal oxide catalyst is obtained and is high in catalytic oxidation activity on carbon monoxide at the low temperature, excellent in water resistance and sulfur resistance and particularly suitable for treatment of complex flue gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst, in particular to a high-entropy metal oxide catalyst, and also relates to a preparation method of the high-entropy metal oxide catalyst and its application in CO catalytic oxidation, belonging to the technical field of flue gas treatment. Background Art

[0002] CO in the sintering flue gas of the iron and steel industry causes serious harm to the environment. To meet the requirements of the green environmental protection policy, flue gas decarbonization treatment is required. At present, the solid catalytic process is widely used in the flue gas treatment of industries such as iron and steel metallurgy and thermal power generation due to its advantages of high CO removal efficiency, low raw material cost, simple operation, and small floor area. In the prior art, precious metal oxides are still commonly used as CO catalysts in iron and steel plants, but their cost is high and the output is low. In recent years, the replacement of precious metals with transition metals as catalysts has become a research hotspot. However, transition metal oxides have defects such as insufficient catalytic activity below 200 °C, poor water resistance, and poor sulfur resistance. Industrial waste gases such as sintering flue gas contain a large amount of water vapor and SO2, which severely restricts their popularization and application in the industrial field. Therefore, improving the activity and stability of transition metals in a low-temperature and humid flue gas environment is a technical problem that urgently needs to be solved at present.

[0003] The literature ("High entropy oxides-exploring a paradigm of promising catalysts: A review", Albedwawi S H, et al., Materials & Design, 2021, 202:109534.) discloses that high-entropy metal oxides (HEOs) exhibit higher oxygen migration rate and oxygen vacancies compared with medium-entropy and low-entropy metal oxides, and the metal dispersion is also better. The complex surface chemical environment and controllable morphology of HEOs provide a new direction for the design of anti-poisoning catalysts. Although HEOs show potential in the fields of catalysis, energy storage, etc., their practical applications still face the following challenges: during the synthesis process of multiple types of metal precursors (5 or more), element segregation is likely to occur due to kinetic differences, resulting in uneven local composition of metal elements. At the same time, under the condition of too high calcination temperature, some metal cations (such as Cu, Co) may migrate or volatilize, or destroy the stability of the high-entropy structure, thereby affecting their catalytic performance. Summary of the Invention

[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a high-entropy metal oxide catalyst, which is composed of multi-metal transition metal oxides and has a special nanosheet structure, showing high catalytic oxidation activity at low temperature for the oxidation of carbon monoxide, and excellent water resistance and sulfur resistance, and is particularly suitable for the treatment of complex flue gas.

[0005] The second object of the present invention is to provide a preparation method of a high-entropy metal oxide catalyst. This method can avoid the agglomeration of nanoparticles formed during the precipitation of metal ions by utilizing the action of a dispersant in combination with the hydrothermal reaction process to obtain a special nanostructure, and can ensure the coprecipitation of multi-metal ions under the condition of high dispersion, improve the distribution uniformity of metal elements, effectively solve the problem that the configurational entropy is not as high as the mixing enthalpy during the preparation of high-entropy metal oxides from multi-component metals, resulting in phase segregation and the generation of secondary phases. Moreover, this method is simple to operate and low in cost, meeting the requirements of industrial production.

[0006] The third object of the present invention is to provide an application of a high-entropy metal oxide catalyst in the catalytic oxidation of carbon monoxide. The high-entropy metal oxide catalyst only contains transition metal element components, greatly reducing its usage cost, and it has excellent catalytic effects on CO components in humid and low-temperature flue gas, and is particularly suitable for the treatment of complex flue gas containing water, sulfur, and low temperature.

[0007] To achieve the above technical objects, the present invention provides a preparation method of a high-entropy metal oxide catalyst. This method involves dissolving copper salt, manganese salt, cerium salt, cobalt salt, vanadium salt and a dispersant in water to form a homogeneous solution, slowly adding an excessive alkali precipitant to the homogeneous solution to form a solid-liquid mixture; transferring the solid-liquid mixture into an autoclave for hydrothermal reaction, and then rapidly cooling. The obtained hydrothermal reaction product is calcined to obtain the high-entropy metal oxide catalyst.

[0008] In the preparation process of the high-entropy metal oxide catalyst of the present invention, various transition metal salts are first uniformly dissolved in water under the action of a dispersant to form a mixed solution with uniformly distributed metal ions. Moreover, due to the wrapping effect of the dispersant on metal ions, the agglomeration of nanocrystallites formed in the subsequent precipitation process can be effectively avoided, and it can ensure that multiple metal ions maintain a highly uniform dispersion state during coprecipitation, preventing the phase separation problem caused by the difference in hydrolysis rates of different metal ions. On the basis of forming a solution with uniformly distributed metal ions, an excessive amount of alkali precipitant is then slowly added. The excessive alkali precipitant can ensure that the solution is in an alkaline environment and reaches the critical value for the coprecipitation of metal ions. By controlling the slow addition of the alkali precipitant, it is beneficial to the uniform nucleation of metal ions and avoids non-uniform nucleation caused by local supersaturation of the alkali precipitant. The solid-liquid mixture containing a large number of nanocrystallites realizes the growth of crystallites under the high-temperature and high-pressure conditions of hydrothermal reaction. However, based on the wrapping effect of the dispersant, the aggregation and growth of nanocrystallites can be continuously inhibited, thereby restricting the excessive growth of crystals to obtain a nanoscale size. At the same time, based on the induction effect of the dispersant, the ordered crystallization of metal oxides is realized, growing into sheet-like nanostructures with special morphologies. After hydrothermal treatment, rapid cooling is carried out. Rapid cooling is easier to maintain a state of uniform mixing of the phases compared to slow cooling, preventing segregation during the cooling process due to the configurational entropy not being able to overcome the mixing enthalpy, and avoiding the adverse effects of secondary phases. The hydrothermal product is further treated by high-temperature calcination to improve the crystal structure of the metal oxide to enhance stability.

[0009] In summary, the high-entropy metal oxide catalyst of the present invention is mainly synthesized by the hydrothermal method. Through in-situ high-pressure crystallization and kinetic control, the uniform mixing of multiple metals, high defect density, and morphology regulation are achieved at the atomic scale. Compared with the multi-metal catalysts directly prepared by traditional coprecipitation or surface impregnation methods, the formed crystal particle size is significantly reduced, so that sheet-like nanostructure crystals are presented. At the same time, the uniform mixing of multi-component metals can be maintained, greatly avoiding phase segregation during the preparation process due to the configurational entropy not being able to overcome the mixing enthalpy and avoiding the adverse effects of secondary phases. The coprecipitation method and the impregnation method are limited by the phase separation tendency and surface limitations and can only be applied to simple systems or supported catalysts.

[0010] Synthesis principle of the high-entropy metal oxide catalyst of the present invention: Five transition metal salts are dissolved in water and form a homogeneous multi-metal mixed solution under the action of a dispersant. Based on the coordination and wrapping effects of the dispersant, and in the high-temperature and high-pressure environment of hydrothermal reaction, the polymerization degree of metal ions decreases, the ionic hydration layer is destroyed, the ionic activity and mobility are significantly improved, and metal ions undergo hydrolysis to form hydroxy complexes (taking Co 2+ and Mn 2+ as examples):

[0011] Mn 2+ +xH2O→[Mn(OH) x(2-x)+ +xH + ;

[0012] Co 2+ +xH2O → [Co(OH) x (2-x)+ +xH + ;

[0013] Hydroxy complexes form oligomers through polycondensation (such as oxygen bridge connection):

[0014] 2[Mn(OH) x (2-x)+ → [M2O y (OH) z 2(2-x)-y +H2O;

[0015] 2[Co(OH) x (2-x)+ → [Co2O y (OH) z 2(n-x)-y +H2O;

[0016] When the supersaturation reaches the critical value, crystal nuclei are formed. The crystal nuclei grow through Ostwald ripening or oriented attachment. The closed environment of the hydrothermal reaction and the encapsulation of the dispersant inhibit particle agglomeration and promote the formation of single crystals or hierarchical structures such as nanosheet structures. For example, a nanosheet structure with a size of about 100 nm is formed, which can expose high-activity crystal planes (such as the spinel {100} crystal plane). The high-entropy effect brings a significant increase in the surface oxygen vacancy concentration, which can be directly used as the CO oxidation activity.

[0017] As a preferred embodiment, the copper salt includes at least one of CuSO4, Cu(NO3)2, and CuCl2.

[0018] As a preferred embodiment, the manganese salt includes at least one of MnSO4, Mn(NO3)2, and MnCl2.

[0019] As a preferred embodiment, the cerium salt includes at least one of Ce(NO3)3, Ce2(C2O4)3, and Ce(C8H 15 O2)3.

[0020] As a preferred embodiment, the cobalt-based salt includes at least one of CoSO4, Co(NO3)2, and CoCl2.

[0021] As a preferred embodiment, the vanadium salt includes at least one of Na3VO4, NH4VO3, and VOSO4.

[0022] ​​​​​​The copper salt, manganese salt, cerium salt, cobalt salt, and vanadium salt involved in the present invention are all conventional water-soluble metal salts.

[0023] As a preferred embodiment, on the basis of the copper salt, manganese salt, cerium salt, cobalt salt, and vanadium salt being measured in equimolar ratio, the molar amount of each metal salt is adjusted within the range not exceeding 25% of the total molar amount of various metal salts.

[0024] As a preferred embodiment, the dispersant includes at least one of polyvinylpyrrolidone, polyethylene glycol, and polyvinyl alcohol. These dispersants all contain a large number of electron-rich heteroatoms and play a complexing role on metal ions. Polyvinylpyrrolidone is preferably used as the dispersant. It contains pyrrolidone groups that can coordinate with high-valent metal ions, which is beneficial to promoting the dispersion of metal ions. At the same time, it can adsorb on the surface of metal oxide nuclei to induce the orderly growth of crystals and improve the crystallization performance.

[0025] As a preferred embodiment, the dosage of the dispersant is 0.3 to 1 times the total molar amount of the copper salt, manganese salt, cerium salt, cobalt salt, and vanadium salt. If the dosage of the dispersant is too low, it is not conducive to the dispersion of metal ions, which will cause agglomeration of nanoparticles during the subsequent precipitation process. At the same time, if the multi-metal ions are not evenly dispersed during coprecipitation, phase separation problems will occur due to the difference in hydrolysis rates of metal ions.

[0026] As a preferred embodiment, the alkali precipitating agent includes at least one of urea, sodium hydroxide, and ammonia water. Urea is preferably used as the alkali precipitating agent. Compared with sodium hydroxide, the decomposition products of urea are gases and will not leave metal ions or other impurities. Compared with ammonia water, solid urea is in a stable state, avoiding pH fluctuations caused by the volatilization of ammonia components.

[0027] As a preferred embodiment, the dosage of the alkali precipitating agent is 6 to 10 times the total molar amount of the copper salt, manganese salt, cerium salt, cobalt salt, and vanadium salt. An excessive amount of the alkali precipitating agent can ensure that the solution is in an alkaline environment until the critical value of coprecipitation of multiple metal ions is reached. It should be noted that the alkali precipitating agent needs to be added slowly to avoid non-uniform nucleation caused by local supersaturation.

[0028] As a preferred embodiment, the conditions of the hydrothermal reaction are: at a temperature of 160 - 200 °C for 6 - 12 h. The conditions of the hydrothermal reaction affect the catalytic activity of the high-entropy metal oxide catalyst. As the temperature of the hydrothermal reaction gradually increases, the catalytic activity of the catalyst gradually increases. When the hydrothermal temperature reaches 180 °C, the catalyst shows the best catalytic activity. Further increasing the hydrothermal reaction temperature, the increase in the catalytic activity of the catalyst is not obvious. This shows that too high or too low hydrothermal reaction temperature will have an adverse effect on the catalytic performance of the catalyst. The optimal hydrothermal reaction temperature range is 160 - 200 °C.

[0029] As a preferred embodiment, the rapid cooling is carried out by water cooling. The time of water cooling is more than 5 hours. The water cooling method has a faster cooling rate compared with other cooling methods such as air cooling. Rapid cooling is more likely to maintain a uniform state of phase mixing than slow cooling, preventing segregation and the adverse effect of secondary phase formation due to the configurational entropy being unable to overcome the mixing enthalpy during the cooling process.

[0030] As a preferred embodiment, the calcination conditions are: calcination at a temperature of 400 - 600 °C for 4 - 6 h. At an appropriate calcination temperature, the products of the hydrothermal reaction, such as metal hydroxides or incompletely crystallized intermediates, can lose bound water, hydroxyl groups, etc., and be transformed into stable metal oxides, strengthening the interaction between metal oxides. At the same time, the organic matter can be oxidized and decomposed during the calcination process to avoid its negative impact on the material properties. The calcination temperature can affect the structure and properties of HEOs: too low a temperature results in low crystallinity, which may cause some precursors to not be completely converted into oxides (such as residual hydroxyl groups), and too high a temperature leads to particle coarsening due to the Ostwald ripening effect and even element segregation. The preferred temperature is 400 - 600 °C, which is particularly suitable for the preparation of HEOs systems and can achieve a balance between high crystallinity and controllable morphology.

[0031] The present invention provides a high-entropy metal oxide catalyst obtained by the preparation method. The Cu-Mn-Ce-Co-V high-entropy metal oxide catalyst synthesized by the hydrothermal method of the present invention has excellent low-temperature activity and resistance to water and sulfur, and is particularly suitable for complex flue gas treatment.

[0032] The high-entropy metal oxide catalyst (HEOs) of the present invention contains multiple transition metals, forming complementary redox cycles, synergistically promoting CO adsorption, O2 activation, and CO2 desorption, forming an efficient catalytic chain. The multi-metal synergistically accelerates the desorption of surface hydroxyl groups and promotes the decomposition of H2O molecules into H + and O - , O - participates in CO oxidation, while H + is rapidly desorbed through surface acid sites, avoiding blockage of active sites. More specifically, it regulates the surface electronic structure by introducing hydrophobic metals Cu and Ce, reducing the competitive adsorption of water molecules at active sites. The doping of Cu and Ce can reduce the coverage of surface hydroxyl groups (-OH), keeping the active sites exposed. It regulates the surface acidity by introducing acidic metal V, enhancing the adsorption of SO2, converting and removing it from the surface (SO2 → SO3), and reducing the coverage of active sites by sulfate deposition. Co easily forms cobalt carbonyl Co2(CO)8, which serves as a highly efficient surface binding site for CO, greatly promoting the surface adsorption and migration of CO. During the redox catalytic cycle process, Mn transforms among multiple valence states such as MnO, Mn2O3, and MnO2, exerting the turnover effect of oxygen species binding and release.

[0033] The present invention also provides an application of a high-entropy metal oxide catalyst, which is used for catalyzing carbon monoxide oxidation. Specifically, it catalyzes the oxidation of carbon monoxide into carbon dioxide.

[0034] The specific surface area of the high-entropy metal oxide catalyst of the present invention is 80-200 m 2 / g, the temperature (T50) corresponding to 50% CO conversion rate is 50-80 °C, and after reacting for 24 h in an environment of 10 vol% H2O and 100 ppm SO2, the CO conversion rate > 90%. Even in a complex flue gas environment containing water and sulfur, after catalytic oxidation by the high-entropy metal oxide, the CO concentration can be reduced to below 1000 ppm, and the removal efficiency is higher than 90%. Under the same experimental conditions, for the Cu-Mn-Ce-Co-V five-component mixed metal oxide prepared by the traditional co-precipitation method, its T50 is 120-150 °C, and the activity decreases by > 30% after reacting for 24 h in an environment of 10 vol% H2O and 100 ppm SO2.

[0035] As a preferred embodiment, the mass of the high-entropy metal oxide catalyst is proportional to the flow rate of the flue gas.

[0036] As a preferred embodiment, the mass space velocity of the flue gas is 25-35 m 3 / (h•kg);

[0037] As a preferred embodiment, the CO concentration in the flue gas is 8000-10000 ppm, that is, 0.8-1.0 vol%, the water vapor concentration is less than or equal to 10 vol%, the SO2 concentration is less than or equal to 300 ppm, and the flue gas temperature range is from room temperature to 200 °C. The flue gas is a by-product discharged at the end of processes such as sintering production in steel plants.

[0038] Compared with the prior art, the innovative beneficial technical effects brought by the technical solution of the present invention:

[0039] The high-entropy metal oxide catalyst provided by the present invention only contains transition metal components and can achieve excellent catalytic effects on CO components in humid low-temperature flue gas.

[0040] The high-entropy metal oxide catalyst provided by the present invention is synthesized by a hydrothermal method. Through in-situ high-pressure crystallization and kinetic control, uniform mixing of multiple metals, high defect density, and morphology regulation are achieved at the atomic scale, which is particularly suitable for synthesizing complex functional materials such as high-entropy oxides. Compared with the multi-metal catalysts directly prepared by traditional co-precipitation or surface impregnation methods, the formed crystal particle size is significantly reduced, resulting in nano-scale particle crystallization. At the same time, it can maintain the uniform mixing of multi-component metals, greatly avoiding the adverse effect of phase segregation and the generation of secondary phases during the preparation process due to the configurational entropy being unable to compete with the mixing enthalpy. In the existing one-step co-precipitation redox-related processes in the preparation of multi-metal oxides, there are defects such as crystal segregation and phase separation during the high-temperature preparation process, which inhibit the synergistic effect of different metal species to form a coupling effect. The appearance of secondary phases reduces the practicality of multi-metal catalysts.

[0041] During the actual application process of the high-entropy metal oxide catalyst provided by the present invention, it shows high efficiency and durability in the CO oxidation reaction in humid sulfur-containing flue gas, and can be used for the oxidative removal of CO components in the flue gas of the steel industry. Compared with the simple metal oxides prepared by the precipitation method or surface impregnation method, the application of HEOs reduces the energy consumption of flue gas treatment, improves the CO removal efficiency, extends the service life of the catalyst and the removal tower, reduces the flue gas treatment cost, and realizes clean production. Description of the Drawings

[0042] Figure 1 SEM images of nano-scale flakes of (CuMnCeCoV)O2 with different magnification sizes prepared in Example 1.

[0043] Figure 2 Process flow chart for catalytic oxidation and removal of CO in flue gas by the high-entropy metal oxide prepared by the present invention.

[0044] Figure 3 Comparison of the reaction activity ( 3 in a) and stability ( Figure 3 in b) of the high-entropy metal oxide catalyst prepared by the present invention and the five-component mixed metal oxide prepared by the one-step co-precipitation method in humid sulfur-containing flue gas (10 vol% H2O, 100 ppm SO2) with a mass space velocity of 30 m Figure 3 / (kg•h) and containing 1 vol% CO.

[0045] Figure 4 Surface imaging diagram of (CuMnCeCoV)O2 prepared in Example 1. It can be seen from the figure that various elements are evenly covered, forming a unified phase system, and can well play the synergistic effect between various elements. Detailed Embodiments

[0046] The following will illustrate specific embodiments to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the scope protected by the claims of the present invention.

[0047] Example 1

[0048] A certain iron and steel plant uses the (CuMnCeCoV)O2 high-entropy transition metal oxide catalyst to treat the CO component in sintering flue gas. The mass space velocity of the flue gas corresponding to the catalyst per unit mass is 30 m 3 / (kg•h), including 1 vol% CO, 7 vol% CO2, 15 vol% O2, 10 vol% H2O, 100 ppm SO2, and the rest is N2.

[0049] The high-entropy metal oxide catalyst is prepared by a hydrothermal synthesis method: Cu(NO3)2, Mn(NO3)2, Ce(NO3)3, Co(NO3)2 and NH4VO3 precursors are mixed in an equimolar ratio (1:1:1:1:1), and stirred and dissolved at 60 °C to form a uniform metal ion solution with an average concentration of 0.1 mol / L. Then, PVP polymer is added as a dispersant and stirring continues. On average, 0.3 mol, that is, 33.3 g of PVP dispersant is added for every 1 mol of metal ions. After the solution becomes clear, an excessive amount of solid urea is slowly added drop by drop (the molar ratio of urea to total metal ions is 6:1) to form a solid-liquid mixture. The solid-liquid mixture is transferred into a hydrothermal reaction kettle and reacted under hydrothermal conditions at 180 °C for 8 h, and then cooled for 6 h. After the obtained solid-liquid mixture is filtered, it is washed successively with deionized water and ethanol, and the obtained intermediate powder product is calcined at 500 °C for 5 h to obtain five high-entropy metal oxide sample materials.

[0050] The high-entropy metal oxide catalytic material synthesized by the hydrothermal synthesis method of the present invention presents a nano-sheet structure with a size of 100 nm, has a smaller crystallinity and obvious lattice fringes, and the active crystal planes are exposed, as Figure 1 shown. This structure greatly improves the effective contact area between its surface and the flue gas. Moreover, the inner side of the mesoporous pore wall constructed on the surface is conducive to gas diffusion and adsorption, thereby effectively increasing the surface saturation adsorption capacity.

[0051] Control group:

[0052] (CuMnCeCoV)O2 as the control group was prepared by the coprecipitation method. The obtained product was compared with the product obtained by the hydrothermal synthesis method to demonstrate the superiority of the high-entropy metal oxide material prepared by the hydrothermal synthesis method. The preparation process of the coprecipitation method is as follows: Similarly, weigh the precursors of Cu(NO3)2, Mn(NO3)2, Ce(NO3)3, Co(NO3)2 and NH4VO3 and mix them in an equimolar ratio (1:1:1:1:1). Similarly, stir and dissolve them at 60 °C to form a homogeneous metal ion solution with an average concentration of 0.1 mol / L. Similarly, add PVP polymer as a dispersant and continue stirring, and add 0.3 mol, that is, 33.3 g of PVP dispersant for every 1 mol of metal ions on average. Similarly, after the solution becomes clear, slowly dropwise add an excessive amount of solid urea (the molar ratio of urea to total metal ions is 6:1). After adding the precipitant to complete the coprecipitation step, a solid-liquid mixture is obtained. The solid-liquid mixture is aged, and the aging conditions are: standing for 1 h at a temperature of 60 °C. The aged solid-liquid mixture is filtered to obtain a composite solid precipitate, which is then washed with deionized water and ethanol respectively. The obtained powder product is also calcined at 500 °C for 5 h to obtain the high-entropy metal oxide material prepared by the coprecipitation method.

[0053] Catalytic experiment:

[0054] During the catalytic oxidation process, the high-entropy metal oxide materials prepared by the precipitation method and the hydrothermal method were successively filled into the CO catalytic combustion tower, and then humidified flue gas containing 100 ppm SO2 at 100 °C was introduced for treatment. All processes were carried out at atmospheric pressure. The initial concentration of CO carbon was about 10,000 ppm, and the CO removal rate of the high-entropy metal oxide material prepared by the precipitation method was less than 40% at this temperature, while the CO removal rate of the high-entropy metal oxide material prepared by the hydrothermal method exceeded 70% under the same conditions. Without using precious metal components, this is a quite good result.

[0055] Example 2

[0056] A certain steel plant used cerium-modified copper-manganese oxide to catalytically remove CO in the tail gas. The filling amount of the catalyst inside the reactor was about 1 kg, the flue gas temperature was 120 °C, and the mass space velocity was controlled at 25 m 3 / (kg•h), including 1 vol% CO, 10 vol% CO2, 10 vol% O2, 10 vol% H2O, 30 ppm SO2, and the rest was N2.

[0057] Mix manganese nitrate monohydrate, copper nitrate pentahydrate, cerium nitrate hexahydrate, cobalt nitrate hexahydrate and ammonium metavanadate precursors in an equimolar ratio (1:1:1:1:1), and stir and dissolve them at 60 °C to form a metal ion solution with an average concentration of 0.1 mol / L. Then add PVP polymer as a dispersant and continue stirring. For every 1 mol of metal ions, 0.3 mol (i.e., 33.3 g) of PVP dispersant is added. After the solution becomes clear, slowly add an excessive amount of solid urea drop by drop (the molar ratio of urea to total metal ions is 6:1) to form a solid-liquid mixture. Transfer the solid-liquid mixture into a hydrothermal reaction kettle and react for 8 h under hydrothermal conditions of 120 °C, 140 °C, 160 °C, 180 °C and 200 °C respectively, and then cool it in water for 7 h. After filtering the obtained solid-liquid mixture, wash it with deionized water and ethanol successively. The obtained powder product is calcined at 500 °C for 5 h to obtain five high-entropy metal oxide sample materials.

[0058] To compare the effects of different hydrothermal reaction temperatures on the CO reaction activity of high-entropy metal oxide materials, all samples were continuously reacted at 120 °C under the condition of 10 vol% H2O - 100 ppm SO2 for 24 h, and the effects on the CO catalytic efficiency were compared. The initial concentration of CO was about 1 vol%. Finally, it was found that the activities of the three groups of samples with hydrothermal temperatures in the range of 160 - 200 °C were significantly higher than those of the other two groups of samples. Among them, the product obtained at a hydrothermal temperature of 180 °C showed the best reaction activity, and still maintained a 91% CO conversion rate after 24 h. The CO conversion rates of the samples obtained under hydrothermal conditions of 120 °C, 140 °C, 160 °C and 200 °C for 24 h were 71%, 77%, 88% and 89% respectively. This shows that too high or too low hydrothermal reaction temperature will have an adverse effect on the catalytic performance, and the optimal hydrothermal reaction temperature range is 160 - 200 °C.

[0059] Example 3

[0060] The CO removal in a certain iron and steel plant depends on a fluidized bed continuous device composed of catalysts filled in a reactor. The flue gas flow rate per unit catalyst is 35 m 3 / (kg•h). Prepare (CuMnCeCoV)O2 high-entropy metal oxide catalyst by hydrothermal synthesis method.

[0061] During the synthesis of high-entropy metal oxides, the synthesis steps of the corresponding intermediate powder products refer to Example 1.

[0062] The obtained intermediate powder products were calcined at 200 °C, 300 °C, 400 °C, 500 °C and 600 °C for 5 h respectively to obtain 5 material samples. The obtained samples were respectively filled in the fluidized bed of the CO catalytic reaction device, and the CO removal efficiency and the catalyst service life of the products obtained at different calcination temperatures were compared under the same environmental conditions. The CO catalytic bed was treated with 1 vol% CO under the conditions of 120 °C, flue gas containing 10 vol% H2O and 100 ppm SO2. The results showed that the corresponding initial CO conversion rates of the five samples were 61%, 71%, 80%, 82% and 79% respectively. The product obtained at the calcination temperature of 500 °C had the best effect. When the temperature was further increased, the corresponding CO conversion rate showed a further downward trend. Moreover, a stability test was carried out on the sample obtained by calcination at 500 °C alone. After reacting at 120 °C for 24 h in a complex environment containing water and sulfur, the conversion rate dropped to 80% and remained stable. The phenomena of water poisoning and sulfur poisoning on the catalyst surface changed from an irreversible process to a reversible process, greatly extending its service life in sintering flue gas.

[0063] The above description is only the preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art of this technology, the improvements and transformations obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A preparation method of a high-entropy metal oxide catalyst, characterized in that: Dissolve copper salt, manganese salt, cerium salt, cobalt salt, vanadium salt and dispersant in water to form a homogeneous solution, and slowly add an excessive amount of alkali precipitant to the homogeneous solution to form a solid-liquid mixture; transfer the solid-liquid mixture to an autoclave for hydrothermal reaction, then rapidly cool it, and calcine the obtained hydrothermal reaction product to obtain a high-entropy metal oxide catalyst.

2. The preparation method of a high-entropy metal oxide catalyst according to claim 1, characterized in that: The copper salt includes at least one of CuSO4, Cu(NO3)2, and CuCl2; and / or, The manganese salt includes at least one of MnSO4, Mn(NO3)2, and MnCl2; and / or, The cerium salts include at least one of Ce(NO3)3, Ce2(C2O4)3, and Ce(C8H 15 O2)3; and / or, The cobalt-based salt includes at least one of CoSO4, Co(NO3)2, and CoCl2; and / or, The vanadium salt includes at least one of Na3VO4, NH4VO3, and VOSO4.

3. The preparation method of a high-entropy metal oxide catalyst according to claim 1 or 2, characterized in that: Based on the copper salt, the manganese salt, the cerium salt, the cobalt salt and the vanadium salt being measured in equimolar ratio, the molar amount of each metal salt is adjusted within the range not exceeding 25% of the total molar amount of various metal salts.

4. The preparation method of a high-entropy metal oxide catalyst according to claim 1, wherein: The dispersant includes at least one of polyvinylpyrrolidone, polyethylene glycol, and polyvinyl alcohol; and / or, The dosage of the dispersant is 0.3 - 1 times the total molar amount of copper salt, manganese salt, cerium salt, cobalt salt and vanadium salt.

5. The preparation method of a high-entropy metal oxide catalyst according to claim 1, characterized in that: The alkali precipitant includes at least one of urea, sodium hydroxide, and ammonia water; and / or, The dosage of the alkali precipitant is 6 - 10 times the total molar amount of copper salt, manganese salt, cerium salt, cobalt salt and vanadium salt.

6. The preparation method of a high-entropy metal oxide catalyst according to claim 1, 4 or 5, wherein: The conditions of the hydrothermal reaction are: at a temperature of 160 - 200 °C, react for 6 - 12 h; and / or, The rapid cooling is carried out by water cooling.

7. The preparation method of a high-entropy metal oxide catalyst according to claim 1, 4 or 5, characterized in that: The conditions of the calcination are: at a temperature of 400 - 600 °C, calcine for 4 - 6 h.

8. A high-entropy metal oxide catalyst, characterized in that: Obtained by the preparation method according to any one of claims 1 - 7.

9. Use of a high-entropy metal oxide catalyst according to claim 8, characterized in that: For catalyzing carbon monoxide oxidation.

10. The application of a high-entropy metal oxide catalyst according to claim 9, wherein: The mass of the high-entropy metal oxide catalyst is proportional to the flow rate of the flue gas; and / or, The mass space velocity of the flue gas is 25 to 35 m 3 / (h·kg); and / or, The concentration of CO in the flue gas is 8000 - 10000 ppm, the concentration of water vapor is less than or equal to 10 vol%, the concentration of SO2 is less than or equal to 300 ppm, and the temperature range of the flue gas is from room temperature to 200 °C.

Citation Information

Cited By

  • High-entropy metal oxide supported nanogold catalyst as well as preparation method and application thereof

    CN121338769A

  • Method for catalytic oxidation of carbon monoxide based on plasma hydroxylation high-entropy metal oxide catalytic material

    CN121467053A